2012
DOI: 10.2147/ndt.s37156
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postpartum depression in a sample of Egyptian women

Abstract: IntroductionPostpartum depression (PPD) represents a considerable health problem affecting women and their families. The aims of this study were to: (a) compare female patients with PPD to normal controls with regard to some biopsychosocial variables, (b) correlate between the severity of PPD and some clinical and biological variables, and (c) to predict some risk factors for PPD.MethodSixty female patients with PPD were compared with 60 healthy postpartum females (control group). Patient and controls were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 47 publications
7
56
0
1
Order By: Relevance
“…A systematic review in six African countries [24] showed incidence rates of the disease from 3.7 to 20.9 % in Nigeria, 5.6 to 20.1 % in Morocco, 3.2 to 6.9 % to The Gambia, 34.7 to 48 % in South Africa, 12 % in Ethiopia and 10 to 43 % in Uganda [24,70]. In Egypt, the disease showed a prevalence of 17.9 % [22].…”
Section: Ppd In Africamentioning
confidence: 99%
See 3 more Smart Citations
“…A systematic review in six African countries [24] showed incidence rates of the disease from 3.7 to 20.9 % in Nigeria, 5.6 to 20.1 % in Morocco, 3.2 to 6.9 % to The Gambia, 34.7 to 48 % in South Africa, 12 % in Ethiopia and 10 to 43 % in Uganda [24,70]. In Egypt, the disease showed a prevalence of 17.9 % [22].…”
Section: Ppd In Africamentioning
confidence: 99%
“…The woman gets hot meals and avoids cold foods and beverages. The woman gets strong criticism by her husband and his family after the birth of a female child which may even lead to a divorce [18,22].…”
Section: Countrymentioning
confidence: 99%
See 2 more Smart Citations
“…Depression symptoms were significantly lowered in mothers who were encouraged to do more skin to skin care (Kymre and Bondas 2013). Hence the mother benefits from the enhanced genetic expression probably by interlink between FADS2 expression, PUFA and postpartum depression (Saleh et al, 2013).…”
Section: Discussionmentioning
confidence: 98%